When the non-contrast-enhanced phase is unnecessary in abdominal computed tomography scans? A retrospective analysis of 244 cases - Costa,Danilo Manuel Cerqueira (2013)
Objective: To evaluate the necessity of the non contrast-enhanced phase in abdominal computed tomography scans. Materials and Methods: A retrospective, cross-sectional, observational study was developed, evaluating 244 consecutive abdominal computed tomography scans both with and without contrast injection. Initially, the contrast-enhanced images were analyzed (first analysis). Subsequently, the observers had access to the non-contrast-enhanced images for a second analysis. The primary and secondary diagnoses were established as a function of the clinical indications for each study (such as tumor staging, acute abdomen, investigation for abdominal collection and hepatocellular carcinoma, among others). Finally, the changes in the diagnoses resulting from the addition of the non-contrast-enhanced phase were evaluated. Results: Only one (0.4%; p > 0.999; non-statistically significant) out of the 244 reviewed cases had the diagnosis changed after the reading of non-contrast-enhanced images. As the secondary diagnoses are considered, 35 (14%) cases presented changes after the second analysis, as follows: nephrolithiasis (10%), steatosis (3%), adrenal nodule (0.7%) and cholelithiasis (0.3%). Conclusion: For the clinical indications of tumor staging, acute abdomen, investigation of abdominal collections and hepatocellular carcinoma, the non-contrast-enhanced phase can be excluded from abdominal computed tomography studies with no significant impact on the diagnosis.